Mobile application for e-saman system - Muhammad Nazmi, Abdul Hadi (2014)
Mobile technology has nowadays become trend in various fields either in business, education, health, engineering, etc. The need of mobility in accomplishing work is increasing as the technology created more advanced mobile devices that are capable in multitasking such as the smartphones. The manual summons system for Security Department of Universiti Malaysia Pahang is an example of manual system that can be transformed into mobile system. The transformation project is called Mobile Application for E-Saman System. The E-Saman System is the summons management system that managed summons records while the mobile application act as the electronic summons recorder. The purpose of developing the application is mainly to assist security officer of UMP Security Department to record summons among students and staffs of UMP. The application will be developing for use on mobile device that run Android operating system platform. The result of developing this application is expected to reduce time consuming in summons activity and provide better data management of summons records.